An easily coatable temperature responsive cholesteric liquid crystal oligomer for making structural colour patterns. Issue 27 (2nd July 2018) - Zhang, Pei; Kragt, Augustinus J. J.; Schenning, Albertus P. H. J.; de Haan, Laurens T.; Zhou, Guofu
Abstract : A crosslinkable, temperature-responsive cholesteric main-chain liquid crystal oligomer was prepared, and used to make patterned coatings. Abstract : A crosslinkable cholesteric main-chain liquid crystal oligomer was prepared, and coated on glass using blade-coating. The coating showed a reflection band that varied as a function of temperature over a range of several hundreds of nanometers. This allowed patterning of the coating in various colours using multiple crosslinking steps at different temperatures.